MEMBANGUN MOTIVASIS KERJA - Mr Mukrodi (Sekolah Menengah Kejuruan (SMK) Pustek, 2019)
The purpose of the organization is profit, and to achieve this requires the participation of employees. But the human resources in question are people who have the enthusiasm of working to achieve goals. Therefore, this research was conducted to analyze the determinants of work motivation, such as the role of leaders and career paths. To be able completing this research, a method is needed, in which the research method is built using reinforcement of the theory (deductive). Then, the quantitative approach was chosen as an effort to explain the direction of the study, which was supported by multiple linear regression analysis. The object of this research is employees in manufacturing companies. The sample technique uses a census with 50 respondents. The results showed that employee morale can be built from the support of clear leadership and career path.